2002
DOI: 10.1021/la010766s
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Decanethiol Adsorption on Au(111):  Extension to 0 °C

Abstract: The coverage-dependent phase behavior of the thiolate formed from decanethiol, CH3(CH2)9SH, on Au(111) was studied at 0 °C using variable-temperature scanning tunneling microscopy and compared to analogous results for temperatures between 25 and 65 °C. At 0 °C, the lowest density striped phase, β, converts to higher density striped phases, δ and χ, at exposures that are significantly less than those required at room temperature. The upright saturation phase, φ, is also obtained with a lower relative exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 29 publications
(58 reference statements)
5
51
0
Order By: Relevance
“…Recent studies revealed that alkylthiols adsorbed on gold form different ordered phases depending on the surface coverage [1][2][3]. A phase diagram was proposed for alkylthiols adsorbed on gold under ultra-high vacuum conditions [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies revealed that alkylthiols adsorbed on gold form different ordered phases depending on the surface coverage [1][2][3]. A phase diagram was proposed for alkylthiols adsorbed on gold under ultra-high vacuum conditions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…A phase diagram was proposed for alkylthiols adsorbed on gold under ultra-high vacuum conditions [1,2]. It was found that at low coverage the alkyl chains were flat on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STM in UHV can give strong imaging signals [35,36]. Tunneling routes between substrate and tip through the substrate molecules is thus feasible and determined by the combined substrate/adsorbate/tip electronic properties.…”
Section: Resultsmentioning
confidence: 99%
“…The self-assembly of alkanethiols into stable monolayers (SAMs) has been studied for many years with Ultra High Vacuum/Scanning Tunnelling Microscopy (UHV/STM) being the diagnostic tool most widely used to determine molecular orientation as a function of coverage (or lateral pressure) and temperature [1][2][3][4] through vapour phase deposition on Au(111). Other techniques employed to probe this system include X-ray Photoelectron Spectroscopy (XPS) [5,6], Low Energy He Atom Diffraction (LEAD) [5] and Atomic Force Microscopy (AFM) [7].…”
Section: Introductionmentioning
confidence: 99%